Present Day Regional Mass Loss of Greenland Observed with Satellite Gravimetry - Schrama, E.J.O. (author); Wouters, B. (author); Vermeersen, L.L.A. (author) (Surveys in Geophysics, 2011)
This paper summarizes results obtained for Greenland’s mass balance observed with NASA’s GRACE mission. We estimate a Greenland ice sheet mass loss at ?201 ± 19 Gt/year including a discernible acceleration of ?8 ± 7 Gt/year2 between March 2003 and February 2010. The mass loss of glacier systems on the South East of Greenland has slowed down while the mass loss increases toward the North along the West side of Greenland. The mass balance can be compared with results obtained by a regional climate model of the Greenland system and ice sheet altimeter data obtained from NASA’s ICEsat mission. Our GRACE-only results differ to within 15% from these independently calculated values; we will comment on the possible causes and the quality of the glacial isostatic adjustment model which is used to correct geodetic datasets. Space Engineering Aerospace Engineering